Kindergartners’ morphological awareness, its instruction and guidance in the Indonesian context - Solehuddin, M.; Gunawan, Wawan; Kurniawan, Eri (Indonesian Journal of Applied Linguistics, 2019)
Children's language development is an arguably integral part of early childhood education. This research departs from the assumption that morphological awareness encompassing sensitivity to word units plays a critical role in ascertaining the success of children's reading skills in school. The purpose of the present study was two-fold: i) to assess the level of morphological awareness of preschool children, and ii) to reveal the types of learning and guidance activities in the classroom that facilitate the development of children's linguistic awareness and early literacy in general. Data were obtained through a set of morphological awareness tasks (a judgment task and a word analogy task) to kindergarten students aged 4-6 years, classroom observations, and interviews with the teachers. By virtue of an exploratory nature of this research, the data stemmed from one kindergarten in a North Bandung area, Indonesia. Findings reveal that the kindergarten children, in general, have demonstrated early signs of morphological awareness owing to ongoing language development. Their morphological awareness level appears to be contingent on the extent of their morphological knowledge. Pedagogically, it is found that the teachers have provided the students with various types of morphological knowledge learning and guidance activities in the school to help hone the awareness. Implicationally, explicit morphological awareness and vocabulary instruction need to be implemented in a preschool context to prepare children’s later academic success.